Prevalence of Effusion in the Tympanic Cavity in Dogs with Dysfunction of the Trigeminal Nerve: 18 Cases (2004–2013). (22nd July 2013) - Kent, M.; Glass, E.N.; de, A.; Platt, S.R.; Haley, A.
<x xml:space="preserve">Abstract</x> Background Animals with disorders involving the trigeminal nerve or its nuclei in the brainstem can have effusion in the tympanic cavity ipsilateral to the side of the neurological deficits. The tensor veli palatini muscle (TVP), innervated by the mandibular branch of the trigeminal nerve, opens the pharyngeal orifice of the auditory tube. With denervation of the TVP, dysfunction of the auditory tube may occur, which could lead to effusion. Hypothesis/Objectives To determine the prevalence of effusion in the tympanic cavity in dogs with disorders involving the trigeminal nerve. Animals Eighteen client‐owned dogs were evaluated retrospectively. Methods Retrospective study. Results Diagnostic imaging databases were searched for dogs having undergone magnetic resonance imaging (MRI) evaluation for signs referable to dysfunction of the trigeminal nerve. Signalment and neurological examination findings were recorded. The MRI study was evaluated for the presence or absence of effusion. MRI characteristics of the affected trigeminal nerve and the muscles of mastication were recorded. Based on the location of the trigeminal nerve lesion, dogs were divided into three categories: brainstem, trigeminal canal, or extracranial. Eighteen dogs met the inclusion criteria. Six of 18 dogs (33%) had effusion in the tympanic cavity ipsilateral to the affected trigeminal nerve. Conclusion and Clinical Importance A substantial proportion of dogs with a lesion affecting the trigeminal nerve had effusion in the tympanic cavity. This finding likely represents denervation of the TVP muscle, which may have led to dysfunction of the auditory tube.